Penerapan Mind Mapping untuk Meningkatkan Motivasi, Kemandirian, dan Hasil Belajar Biologi XI IPA Gunungsitoli Idanoi - Erlina Zebua (Program Studi Pendidikan Biologi - Universitas Nias, 2024)
Low learning motivation, limited learning independence, and poor Biology learning outcomes remain critical challenges in secondary education, particularly when instructional practices are still dominated by conventional methods that inadequately engage students in active learning. This study aimed to analyze the effectiveness of the Mind Mapping learning method in improving learning motivation, learning independence, and Biology learning outcomes among eleventh-grade science students at SMA Negeri 1 Gunungsitoli Idanoi in the 2023/2024 academic year. The study employed a Classroom Action Research design based on the Kemmis and McTaggart model, implemented through two cycles consisting of planning, action, observation, and reflection stages. Data were collected through observation, questionnaires, achievement tests, and documentation, and were analyzed using descriptive quantitative and comparative approaches across cycles. The findings revealed that the implementation of Mind Mapping increased students’ learning motivation from 62.43% to 89.12%, learning independence from 67.21% to 88.28%, and average learning outcomes from 69.52 to 81.8, while classical learning mastery improved from 59% to 88%. Hypothesis testing demonstrated that all indicators significantly achieved the predetermined targets at a 95% confidence level. These findings confirm that Mind Mapping is an effective instructional strategy for fostering more active, independent, and meaningful Biology learning.